Antioxidant properties of flavonoid derivatives and their hepatoprotective effects on CCl4 induced acute liver injury in mice. Issue 28 (24th April 2018) - Xiang, Cen; Teng, Yuou; Yao, Chaoran; Li, Xuehui; Cao, Menglin; Li, Xuzhe; Pan, Guojun; Lu, Kui; Galons, Hervé; Yu, Peng
Abstract : Excessive accumulation of free radicals in the body can cause liver damage, aging, cancer, stroke, and myocardial infarction. Abstract : Excessive accumulation of free radicals in the body can cause liver damage, aging, cancer, stroke, and myocardial infarction. Anastatin B, a skeletal flavonoid, was reported to have antioxidant and hepatoprotective effects. Anastatin B derivatives, compound1 and2, were synthesized by our group previously. In this study, their antioxidant activity and hepatoprotective mechanism were studied using chemical evaluation methods, a cellular model of hydrogen peroxide (H2 O2 )-induced oxidative damage, and a mouse model of carbon tetrachloride (CCl4 )-induced liver injury. Results from the chemical evaluation suggested that both compounds had good antioxidant power and radical scavenging ability in vitro . MTT assay showed that both compounds had cytoprotective activity in H2 O2 -treated PC12 cells. Moreover, their hepatoprotective activities evaluated using a mouse model of CCl4 -induced liver injury that compared with the model group, pretreatment with compound1 and2 significantly decreased alanine transaminase (ALT), aspartate transaminase (AST), lactate dehydrogenase (LDH), and malondialdehyde (MDA) levels; reduced the liver tissue damage; and increased glutathione content. However, compound2 was a more effective hepatoprotectant than compound1 was. Finally, the amount of TNF-α and cytochrome P450 2E1 (CYP2E1) were significantly downregulated in compound1 and2 pretreatment groups. Collectively, our findings demonstrate that both compounds have potential antioxidant activity and hepatoprotective effect in vitro and in vivo . Further chemo-biological study and investigation of the compounds' enzymatic targets are ongoing.